2022
DOI: 10.1186/s12989-022-00487-6
|View full text |Cite
|
Sign up to set email alerts
|

Grouping MWCNTs based on their similar potential to cause pulmonary hazard after inhalation: a case-study

Abstract: Background The EU-project GRACIOUS developed an Integrated Approach to Testing and Assessment (IATA) to support grouping high aspect ratio nanomaterials (HARNs) presenting a similar inhalation hazard. Application of grouping reduces the need to assess toxicity on a case-by-case basis and supports read-across of hazard data from substances that have the data required for risk assessment (source) to those that lack such data (target). The HARN IATA, based on the fibre paradigm for pathogenic fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…This may suggest that the more rigid NM-401 fibers induce cellular membrane damage which may contribute to the enhanced effects observed by these fibers. In agreement with our findings, a grouping effort of MWCNT for risk assessment (69) conclude that NM-400 occurs as tangled agglomerates which are not able to induce frustrated phagocytosis (65), while NM-401 cause lysosomal disruption, intracellular 'vesicle escape' (66) and frustrated phagocytosis in macrophages both in vitro and in vivo (65). As several studies have demonstrated that MWCNT-induced fibrosis is Th2-type response mediated (reviewed in 38), the involvement of M2 polarization events has been suggested (35)(36)(37).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may suggest that the more rigid NM-401 fibers induce cellular membrane damage which may contribute to the enhanced effects observed by these fibers. In agreement with our findings, a grouping effort of MWCNT for risk assessment (69) conclude that NM-400 occurs as tangled agglomerates which are not able to induce frustrated phagocytosis (65), while NM-401 cause lysosomal disruption, intracellular 'vesicle escape' (66) and frustrated phagocytosis in macrophages both in vitro and in vivo (65). As several studies have demonstrated that MWCNT-induced fibrosis is Th2-type response mediated (reviewed in 38), the involvement of M2 polarization events has been suggested (35)(36)(37).…”
Section: Discussionsupporting
confidence: 93%
“…For MWCNT, a progression from acute inflammation to chronic fibrotic changes suggests that a resolution of inflammation involving Th2 responses may underlie the fibrotic events (38). It is also evident that long and rigid MWCNT typically induce more prominent inflammation and fibrotic responses than shorter coiled MWCNT (61,64,69). In agreement, this study showed that the long and rigid NM-401 fibers gave more severe effects on macrophage markers, as illustrated by increased M2 markers Arg1, Ear11, and Mrc1, and cytokine secretion, compared to the shorter and more coiled NM-400 fibers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] Moreover, presence of multinucleated macrophages in lungs has been previously associated with frustrated phagocytosis and clearance issue following the inhalation of high aspect ratio materials (HARN) such as long MWCNTs. [ 41,42 ] Herein, only the largest material namely LGO (≈8 µm), but not LFLG (≈1 µm), led to the formation of multinucleated macrophages, suggesting that only this material could not be cleared properly from the lungs, in agreement with the HARN frustrated phagocytosis paradigm and its associated 5 µm threshold. [ 18,41,42 ]…”
Section: Resultsmentioning
confidence: 69%
“…This is in sharp contrast to the response found for the positive control, namely long and rigid MWCNTs, which have been repeatedly reported to induce chronic inflammation, fibrosis, tissue remodeling, and even cancer. [41,42] However, the presence of multinucleated macrophages, granulomalike structures, and persistent material agglomerates in LGOtreated mouse lungs warrants further investigations, in particular to assess the long-term fate and possible consequences of these biopersistent materials in the lungs.…”
Section: Biological Response In Lung Tissuesmentioning
confidence: 99%
“…Another work includes the testing of the high aspect ratio nanomaterials (HARNs) IATA [ 5 ]. Murphy and co-authors tested 15 different multiwalled carbon nanotubes (MWCNT) demonstrating the successful application of the HARN IATA to group some MWCNT with a similar hazard potential after inhalation exposure, while discriminating from others without a similar inhalation hazard [ 56 ].…”
Section: Resultsmentioning
confidence: 99%